Rp-Hplc Method For Quantitative Estimation Of Olanzapine In Tablet Dosage Forms - A.RUKMANGADA RAO; N.DELHI RAJ; JAGADEESH (International Journal of Pharma and Bio Sciences, 2012)
A simple RP-HPLC method for the determination of olanzapine in pharmaceutical dosage forms. Numerous HPLC conditions were tested for determination of olanzapine. The best result was achieved by using Capcell pak C-18 (250×4.6mm) 5µm column and a mobile phase consisting of Acetonitrile: Water: Tri ethylamine (60:40:0.1 v/v/v), a flow rate of 1.0 ml/min with ultraviolet detection at 270nm. The retention time of the drug was 6.53 min. The method produced liner responses in the concentration range of 2 to 12µg/ml of olanzapine. The method was found to be applicable for determination of the drug in tablets.